Development of a Snakes and Ladders Media for Addition and Subtraction Material to Increase the Learning Interest of Grade II Students at SD Negeri 16 Sitiung - Hasibuan, Rusdi Indra; Lutfiah, Zumrotun; Nopiyanti, Meta (The Future of Education Journal, 2025)
This research is motivated by issues in the implementation of the second-grade mathematics learning process, particularly in SD Negeri 16 Sitiung, where several factors were found to contribute to students' lack of enthusiasm for learning. One of the main causes identified is the teacher's use of only the lecture method and workbooks (LKS) without any learning media, which leads to students' disinterest and lack of motivation to study. The effort to address this issue is to develop a Snakes and Ladders learning media, which can enhance students' learning outcomes by using an engaging and interactive medium. This study aims to produce a valid, practical, and effective Snakes and Ladders media for teaching addition and subtraction in second-grade students at SD Negeri 16 Sitiung. This research uses the Research and Development (R&D) method. The development model selected is ADDIE, which consists of five stages: Analyze, Design, Development, Implementation, and Evaluation. The data types used in this study are both qualitative and quantitative. The instruments developed include observation sheets, interview guidelines, validity instruments, practicality instruments, and effectiveness instruments. Data collection techniques involve interviews and observations. Data analysis includes validation, practicality, and effectiveness results. The results of this research and development yielded teaching materials in the form of a Snakes and Ladders media for mathematics learning, specifically for addition and subtraction in second-grade students at SD Negeri 16 Sitiung. Based on validation from 4 validators, the average score percentage was 86.6%, and the Snakes and Ladders media was rated 98.2% by students as very practical. Educators gave a 100% rating, categorizing it as very practical. The effectiveness of the Snakes and Ladders media was rated at 90%, indicating that it is effective.